2020
DOI: 10.3389/fbioe.2020.00732
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed PEEK Extravascular Stent in the Treatment of Nutcracker Syndrome: Imaging Evaluation and Short-Term Clinical Outcome

Abstract: Minimally invasive options are safe and reliable alternatives for the treatment of nutcracker syndrome (NCS). After continued efforts, our team successfully devised a new and effective therapeutic method: 3D-printed extravascular stenting of the left renal vein. From December 2017 to May 2019, 28 patients (25 men and 3 women) from different parts of China between 18 and 37 years old (mean, 23.6 years) diagnosed with NCS were admitted for laparoscopic 3D-printed extravascular stenting treatment. The post-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…The possibility of graft deformation, migration, and restenosis of the LRV still needs to be investigated. To solve these problems, our team proposed the technique of 3DP-EXVS to treat NCS ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of graft deformation, migration, and restenosis of the LRV still needs to be investigated. To solve these problems, our team proposed the technique of 3DP-EXVS to treat NCS ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyetheretherketone has the advantages of radiation permeability and no artifacts in magnetic resonance scanning, which can better evaluate postoperative recovery ( Fairag et al, 2021 ; Han et al, 2022 ). It has been used in artificial joint jaws, skulls, and spines: lumbar spine, oral defect repair, and other fields ( He et al, 2020a ; Li et al, 2021a ; Li et al, 2022a ). Also, compared with traditional metal materials (stainless steel, titanium alloy) implanted into human body, polyetheretherketone has good biocompatibility, and its elastic modulus is comparable to human cortical bone ( He et al, 2020a ; Li et al, 2021a ).…”
Section: Polymer Materials For 3d Bio Printing Of Bone and Cartilagementioning
confidence: 99%
“…It has been used in artificial joint jaws, skulls, and spines: lumbar spine, oral defect repair, and other fields ( He et al, 2020a ; Li et al, 2021a ; Li et al, 2022a ). Also, compared with traditional metal materials (stainless steel, titanium alloy) implanted into human body, polyetheretherketone has good biocompatibility, and its elastic modulus is comparable to human cortical bone ( He et al, 2020a ; Li et al, 2021a ). It can effectively reduce the stress shielding effect after implantation into the human body.…”
Section: Polymer Materials For 3d Bio Printing Of Bone and Cartilagementioning
confidence: 99%
“…Till date, a total of 15 studies have reported the clinical outcomes and complications of 100 patients using laparoscopic or robot‐assisted extravascular stent for NCS 5,7–20 . Of the enrolled patients, 98 (98%) had complete symptom resolution or significant symptom improvement, and 2 (2%) had no symptom improvement because of the extravascular stent migration during follow‐up 5,7–20 . However, due to small sample size (1–28 patients) and short follow‐up time, long‐term results remain largely unreported.…”
Section: Introductionmentioning
confidence: 99%